Research on the training system of reserve talents of police College in universities from the perspective of integration of sports and education - Chen, Zhijun; Mao, Jun; Guan, NongQin; Chen, Qiuyi (Quality in Sport, 2025)
This study focuses on the construction of reserve talents training system of university police college under the perspective of sports and education integration. Under the background of the current education reform, the integration of sports and education, as an important way to improve the comprehensive quality of students, is particularly key to the police college. This paper deeply probes into the current situation and existing problems of reserve talent training in university police college, and puts forward some strategies, such as integrating sports and police education, optimizing curriculum setting and teaching methods, strengthening practical teaching and training base construction. The research results show that the training system of reserve talents in the perspective of the integration of sports and education not only significantly improves the students’ physical fitness and police skills, but also enhances their teamwork ability and practical coping ability, which provides a strong support for the training of police talents in the new era.